An experimental study of an efficient supercapacitor stacking scheme to power mobile phones - Monteiro, J.; Garrido, N.; Fonseca, R. A. (IEEE 33rd International Telecommunications Energy Conference (INTELEC), 2011)
This paper presents an implementation of a solution for efficiently using supercapacitors to power mobile phones. This system achieves an increase in the autonomy of the device by maximizing the energy harnessed from the supercapacitors. Test results confirm the uplift in the device's autonomy by using a supercapacitor stacking scheme, when comparing with the use of a DC/DC voltage converter alone. A specific charging scheme for this solution is also prototyped, allowing ultrafast and incremental charges without affecting the scheme's operability.